The new cosmos answering astronomy's big questions - Eicher, David J. 1961- (Cambridge University Press, 2015)
Over the past decade, astronomers, planetary scientists, and cosmologists have answered - or are closing in on the answers to - some of the biggest questions about the universe. David J. Eicher presents a spectacular exploration of the cosmos that provides you with a balanced and precise view of the latest discoveries. Detailed and entertaining narratives on compelling topics such as how the Sun will die, the end of life on Earth, why Venus turned itself inside-out, the Big Bang Theory, the mysteries of dark matter and dark energy, and the meaning of life in the universe are supported by numerous color illustrations including photos, maps and explanatory diagrams. In each chapter the author sets out the scientific history of a specific question or problem, before tracing the modern observations and evidence in order to solve it. Join David J. Eicher on this fascinating journey through the cosmos!
Title from publisher's bibliographic system (viewed on 10 Dec 2015)
Keywords: Astronomy; Cosmology